Fuzzy logic control implementation on arduino uno based automatic window system - Yudi Wijanarko (International Journal Cister, 2023)
The window is the most important unit in building construction as a place for light and air circulation from inside and outside the building. Technological advances greatly affect everyday human life, humans are greatly facilitated by the presence of technology, one of which is the merging of windows with technology into Automatic Windows that can open and close automatically using Photodiode as input with Arduino Uno as a control system. Using fuzzy logic as a basis for decision makers in different circumstances at one time is very suitable as a method in this research.